APLIKASI STOK BARANG CV. ADICITA PRAYOGA BERBASIS WEB - NOVITA SETIANTI; Wika Purbasari; Sunaryono Sunaryono (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2022)
Inventory system on CV. Adicita Prayoga still uses a manual system, using paper stock forms. With this manual data processing process, there is often a difference and data duplication (redundancy) in stock of goods, so that data and information on the end of stock or inventory produced sometimes do not match the physical stock in the warehouse. Then on incoming goods transactions and outgoing goods transactions, errors in recording and archiving transaction data often occur, thus hampering the reporting process that will be given to management as material for consideration of company policies. System development in developing this application, the methodology used is the waterfall model. The stages in the waterfall model must be completed one by one sequentially from the initial stage to the final stage. The system that can support the stock of goods at CV. Adicita Prayoga is to create a stock application program for CV. Adicita Prayoga, so that it can facilitate data processing and stock items. The current inventory control inventory system is still done manually, therefore the author makes an inventory control inventory application system in the hope of minimizing the shortage of production raw material stocks and the accumulation of unused goods in the warehouse. With the use of a minimum inventory limit, the inventory and quality of goods in the warehouse can be maintained